Body Image and its Relationship to Life Orientation Among Female Fitness Center Attendees in Irbid Governorate - Jarwan, Ali; Amoorah, Tasneem; Almomani, Doha (Jordan Journal of Educational Sciences, 2025)
Objectives: The study aims to explore the level of body image and its relationship to life orientation among female fitness center attendees in Irbid Governorate, Jordan, as well as to examine if there are statistically significant differences based on variables such as age, marital status, education level, and employment status. Methodology: A descriptive correlational method was applied, using body image and life orientation scales on a sample of 347 female fitness center attendees from Irbid Governorate in Jordan, selected through convenience sampling. Results: The results revealed that the level of body image perception among fitness center attendees was high. No statistically significant differences were found in body image scores across all dimensions based on age. Additionally, no significant differences were found based on marital status in all dimensions, except for the general feelings about appearance dimension, where single individuals scored higher. There were no significant differences based on educational level in all dimensions, except for the weight satisfaction dimension, where those with a bachelor’s degree or higher scored higher. No statistically significant differences were found based on employment status across all dimensions, except for the general feelings about appearance, where students scored higher. The results also indicated a high level of life orientation, with no significant differences based on age or marital status. Significant differences were found based on education level, with individuals holding a bachelor’s degree or higher scoring higher, and based on employment status, where employed individuals scored higher. Finally, the results revealed a statistically significant positive relationship between body image and life orientation among fitness center attendees. Conclusion: The study concludes that there is a need to enhance awareness regarding body image and positive life orientation by adopting positive life approaches and practices. Keywords: Body Image, Life Orientation, Female Fitness Center Attendees.